Application and Scope of Schreiber's Gold(I)‐Catalyzed α‐Pyrone Synthesis to Ring A Aromatic Podolactones. Issue 26 (22nd July 2014) - Sánchez‐Larios, Eduardo; Giacometti, Robert D.; Hanessian, Stephen
Abstract: Schreiber's gold(I)‐catalyzed synthesis of α‐pyrones was adapted to the total synthesis of a ring A aromatic podolactone, urbalactone. The scope of the acetylenic ester partner in the formation of α‐pyrones was studied. The total synthesis features, as key steps, α‐pyrone formation, Friedel–Crafts cyclization, Stille coupling, and a N, N′ ‐dicyclohexylcarbodiimide/4‐( N, N ‐dimethylamino)pyridine lactonization to generate the γ‐lactone. Several α‐pyrone intermediates from this work exhibited in vitro antiproliferative activity against the A2780 ovarian cancer cell line. Abstract : Schreiber's gold(I)‐catalyzed synthesis of α‐pyrones is adapted to the total synthesis of a ring A aromatic analog of urbalactone. The scope of the acetylenic ester partner in the formation of α‐pyrones is also studied. Notably, several α‐pyrone intermediates from this work exhibit in vitro antiproliferative activity against the A2780 ovarian cancer cell line.